The reference wars: Encyclopædia Britannica's decline and Encarta's emergence - Greenstein, Shane (Strategic Management Journal, 2017)
Research summary: The experience of Encyclopædia Britannica provides the canonical example of the decline of an established firm at the outset of the digital age. Competition from Microsoft's Encarta in 1993 led to sharp declines in the sales of books, which led to the distressed sale of the firm in 1996. This article offers new source material about the actions at both Encarta and Britannica, and it offers a novel interpretation of events. Britannica's management did not misperceive the opportunities and threats, and Britannica did not lack technical prowess. This narrative stresses that Britannica's management faced organizational diseconomies of scope between supporting lines of business in the old and new markets, which generated internal conflicts. These conflicts hindered the commercialization of new technology and hastened its decline . Managerial summary: An established and leading firm, such as Encyclopædia Britannica, would seem to have enormous advantages over its competitors in a new market. Why would a successful firm come to have severe difficulties organizing for a new market? Of particular importance for explaining Britannica's decline are theories that stress its inherited capabilities, especially inherited technological (in)abilities and inherited (mis)perceptions about the potential for new market opportunities. This article argues that Britannica's management did not misperceive the opportunities and threats, and Britannica did not lack technical prowess. This narrative stresses that Britannica's management faced organizational diseconomies of scope between supporting lines of business in the old and new markets, which generated internal conflicts. The narrative directs attention at managing commercialization activity around new products using new technologies . Copyright © 2016 John Wiley & Sons, Ltd.